Evaluation of iodine nutritional status during pregnancy by estimated 24-h urinary iodine excretion: population variation range and individual accuracy. Issue 2 (12th February 2022) - Bu, Ye; Cai, Yan; Ji, Chunlei; Zhao, Chunyan; Tian, Chunyuan; Pang, Bo; Shi, Mengqi; Li, Xin; Liu, Ying; Sun, Dianjun
Abstract: Objective: To explore the accuracy of estimated 24-h urinary iodine excretion (24-h UIEest ) in assessing iodine nutritional status. Design: Fasting venous blood, 24-h and spot urine samples were collected during the day. The urinary iodine concentration (UIC) and urinary creatinine concentration (UCrC) were measured, and the urinary iodine-to-creatinine ratio (UI/Cr), 24-h UIEest, and 24-h urinary iodine excretion (24-h UIE) were calculated. At the population level, correlation and consistency between UIC, UI/Cr, 24-h UIEest and 24-h UIE were assessed using correlation analysis and Bland–Altman plots. At the individual level, receiver operating characteristic (ROC) curves were used to analyse the accuracy of the above indicators for evaluating insufficient and excessive iodine intake. The reference interval of 24-h UIEest was established based on percentile values. Setting: Indicator can accurately evaluate individual iodine nutrition during pregnancy remains controversial. Participants: Pregnant women ( n 788). Results: Using 24-h UIE as standard, the correlation coefficients of 24-h UIEest from different periods of the day ranged from 0·409 to 0·531, and the relative average differences ranged from 4·4 % to 10·9 %. For diagnosis of insufficient iodine intake, the area under the ROC curve of 24-h UIEest was 0·754, sensitivity and specificity were 79·6 % and 65·4 %, respectively. For diagnosis of excessive iodine intake, the area of 24-h UIEest was 0·771, sensitivity and specificity were 66·7 % and 82·0 %, respectively. The reference interval of 24-h UIEest was 58·43–597·65 μg. Conclusions: Twenty-four-hour UIEest can better indicate iodine nutritional status at a relatively large sample size in a given population of pregnant women. It can be used for early screening at the individual level to obtain more lead time for pregnant women.